Poetic process and the place of artistic production in Contemporary Art an artist’s experience (Revista Apotheke, 2023)
In the current research, it is predicted that contemporary art may be produced in different places, not only in traditional institutions but also in non-traditional ones. The paper is divided into three sections. Firstly, I relate distinctive poetic experiences throughout my artistic career to intrinsic problems that came out of each context in which the projects were contrived and carried out. Secondly, I suggest that all projects mentioned in this study show great potential for reflection on new ways of dealing with artistic productions employing collaboration. Finally, I discuss that the place of artistic production and the exhibition of visual arts nowadays interfere directly with the possibilities of collaborative agency strategies as a poetic tool. In this sense, in addition to art galleries and museums, art studios and classrooms may also be considered important places to produce and present contemporary art.
Keywords: Contemporary Art; poetic experience; place of production; collaborative art